2013
DOI: 10.1111/add.12104
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol—a universal preventive agent? A critical analysis

Abstract: Background In observational studies, moderate drinking is associated with a reduced risk of more than twenty different diseases and health problems. However, it would be premature to conclude that there is a causal relationship. Method This paper critically reviews the evidence for such associations. Findings It was found that reasons for questioning the causal association of moderate drinking and a reduced health risk are: the lack of dose-response relationships; the characteristics and lifestyles of today's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 94 publications
3
91
0
1
Order By: Relevance
“…Conversely, epidemiological studies suggest moderate alcohol intake has multiple beneficial effects (1,2). The epidemiological study of Marmot and Brunner in 1991 revealed a J-shaped relationship between alcohol intake and the risks of mortality due to cardiovascular disease and cancer (3).…”
mentioning
confidence: 99%
“…Conversely, epidemiological studies suggest moderate alcohol intake has multiple beneficial effects (1,2). The epidemiological study of Marmot and Brunner in 1991 revealed a J-shaped relationship between alcohol intake and the risks of mortality due to cardiovascular disease and cancer (3).…”
mentioning
confidence: 99%
“…Les effets nocifs de la consommation d'alcool sur la santé pourraient être sous-estimés par rapport à ceux découlant du tabagisme : on a estimé qu'en 2000 l'alcool avait entraîné une charge mondiale de morbidité semblable à celle du taba gisme 8,48 . Les résultats récents en recherche ne montrent pas que la consommation d'alcool aurait des effets protecteurs sur l'organisme 18, [50][51][52] et certaines études antérieures ayant étayé l'existence d'« effets protecteurs » de la consommation d'alcool étaient défaillantes sur le plan méthodologique [53][54][55][56][57][58] -en fait, ce sujet demeure controversé 51,55,[59][60][61][62] . Une grande proportion de participants à l'étude ont indiqué consommer de l'alcool en quantité faible ou modérée (0,1 à 29,9 g d'éthanol par jour ou de moins de 1 verre par jour à 2 verres par jour) et pourraient ne pas être conscients des effets néfastes potentiels de quantités d'alcool dans l'organisme certes faibles mais régulières.…”
Section: Habitudes De Consommation D'alcoolunclassified
“…This assumption is based on the curve-linear relationship that is often observed between alcohol consumption and various health measures, where low drinkers tend to have worse health than moderate drinkers. Some argue that this favourable outcome among moderate drinkers is due to a genuine healthpromoting effect of alcohol (Vahtera et al, 2002), while others believe that these findings are more likely due to unmeasured confounding (Andreasson, 2007, Fekjaer, 2013, Holder, 2007, Klatsky, 2007. By using twin data, it is possible to investigate this association between alcohol consumption and a chosen health measure to examine whether the association is influenced by genetic confounding.…”
Section: Example 3 -Alcohol Consumption and Sick Leavementioning
confidence: 99%